2010
DOI: 10.4196/kjpp.2010.14.1.15
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modulation of hnRNP L Levels on the Decay of bcl-2 mRNA in MCF-7 Cells

Abstract: It has been shown that CA repeats in the 3'-untranslated region (UTR) of bcl-2 mRNA contribute the constitutive decay of bcl-2 mRNA and that hnRNP L (heterogenous nuclear ribonucleoprotein L) interacts with CA repeats in the 3'-UTR of bcl-2 mRNA, both in vitro and in vivo. The aim of this study was to determine whether the alteration of hnRNP L affects the stability of bcl-2 mRNA in vivo. Human breast carcinoma MCF-7 cells were transfected with hnRNP L-specific shRNA or hnRNP L-expressing vector to decrease or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…The stability of the antiapoptotic gene BCL2 was previously reported to be regulated by hnRNPL, which prevents the trigger of the NMD by directly interacting with the longer 3′UTR of the gene [ 16 ]. However, the study from Lim and colleagues suggested that the 3′UTR splicing of BCL2 is independent of hnRNPL in MCF-7, proposing the presence of an unknown factor interacting with the hnRNPL in the regulation of this splicing event [ 50 ]. In our data, the shortening of the BCL2 isoform, as well as the gene downregulation, is coherent with the impairment of hnRNPL-mediated stability, which could be directly mediated by the interaction with DSCAM-AS1 .…”
Section: Discussionmentioning
confidence: 99%
“…The stability of the antiapoptotic gene BCL2 was previously reported to be regulated by hnRNPL, which prevents the trigger of the NMD by directly interacting with the longer 3′UTR of the gene [ 16 ]. However, the study from Lim and colleagues suggested that the 3′UTR splicing of BCL2 is independent of hnRNPL in MCF-7, proposing the presence of an unknown factor interacting with the hnRNPL in the regulation of this splicing event [ 50 ]. In our data, the shortening of the BCL2 isoform, as well as the gene downregulation, is coherent with the impairment of hnRNPL-mediated stability, which could be directly mediated by the interaction with DSCAM-AS1 .…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, a gene from the Bcl family of genes that encodes specific protein, which regulates programmed cell death in pathological, and pathological conditions, is a representative anti-apoptotic protein; the levels of Bcl-2 affects cellular fates, death, or survival (Lim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The continued existence of CDK4 has been associated with maintenance of tumor cell proliferation (Yu et al, 2006). P53 is a transcription factor that senses DNA damage, DNA repair, cell apoptosis, and cell cycle arrest; moreover, inactivating mutations of Bcl-2, a gene from the Bcl family of genes that encodes specific protein, which regulates programmed cell death in pathological, and pathological conditions, is a representative anti-apoptotic protein; the levels of Bcl-2 affects cellular fates, death, or survival (Lim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50% of t(14:18) translocations associated with B cell lymphoma occur in the BCL2 major breakpoint region (MBR), fusing a portion of the IGH locus on chromosome 14 to the last exon of BCL2 on chromosome 18 and causing BCL2 transcriptional activation by the IGH l enhancer (Cleary et al, 1986;Seto, 2002;Deng et al, 2007). At the mRNA level, MBR translocations preserve the BCL2 ORF, TC, and proximal~2,500 nt of its 3 0 UTR (including protective hnRNP L binding sites), but the distal half of the BCL2 3 0 UTR is replaced by 4-6 IGH exons, depending on which IGH polyadenylation signal is used ( Fig 5B; Cleary et al, 1986;Lim et al, 2010). These exons are efficiently spliced and would be expected to lead to EJC deposition and NMD.…”
Section: Of 19mentioning
confidence: 99%